2019
DOI: 10.1108/ilt-04-2019-0114
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tribological property of self-lubrication CBN abrasive composites containing molybdenum disulfide

Abstract: Purpose This paper aims to evaluate the influence of molybdenum disulfide (MoS2) concentrations (5, 7.5, 10, 12.5 and 15 Wt.%) on the microstructure and tribological property of the self-lubrication cubic boron nitride (CBN) abrasive composites. Design/methodology/approach Three point bending method and rotating sliding test are used to evaluate the flexural strength and tribological property of self-lubricating CBN abrasive composites. Microstructure, wear morphology of the ball and scratch are supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…High carbon equivalent gray cast iron (HCEG-CI) contained with over 3.6% carbon equivalent has been widely used to fabricate brake components in auto industry owing to its high wear resistance ability and excellent thermal conductivity [1][2][3] . However, the mechanical properties of HCEGCI materials are severely affected due to the existence of lamellar graphite particles [4] . Numerous published studies reported that the mechanical properties of HCEGCI materials could be further improved by employing various alloy elements [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…High carbon equivalent gray cast iron (HCEG-CI) contained with over 3.6% carbon equivalent has been widely used to fabricate brake components in auto industry owing to its high wear resistance ability and excellent thermal conductivity [1][2][3] . However, the mechanical properties of HCEGCI materials are severely affected due to the existence of lamellar graphite particles [4] . Numerous published studies reported that the mechanical properties of HCEGCI materials could be further improved by employing various alloy elements [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…There are various solid lubricants are used, namely, MoS 2 , WS 2 , FeS 2 , hexagonal boron nitride and synthetic graphite (Singh et al, 2020). Metal sulfides are used lubricants for its hightemperature lubricity due to good d-spacing (Zhao et al, 2019;Gradt and Schneider, 2016). Though the abrasives boost m, remove the glaze and thermally decomposed layer formed by the carbonaceous film developed on the counterpart, but increase wear rate on both surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al used graphite particles to improve the performance of metal-bonded high-speed grinding wheels [16]. Zhao et al used MoS 2 particles to enhance tribological properties of cubic boron nitride abrasive composites[17]. In another study, Miao et al recommended that TiX additives in the Ag-Cu-Ti matrix (TiB 2 , TiN, and TiC) improve the shear strength of the brazed joints[18].…”
mentioning
confidence: 99%